(untitled) (Psicologia USP, 2006)
The Visual Evoked Potential (VEP) is a cortical response obtainable on the scalp. It usually reflects the activity from V1 neurons. It is classified in transient or steady-state, according with the temporal frequency of stimulation. Other stimuli properties evoke a selective activity from different neuronal groups found in V1. This way, VEP have been used to study luminance and chromatic human vision. Several studies used VEP to estimate luminance contrast sensitivity in the spatial frequency domain. More recently, some studies used VEP to measure color discrimination thresholds. The transient VEP shows a good agreement with psychophysical measurements of spatial luminance contrast sensitivity and color discrimination, being a noninvasive method to study vision from subjects with difficulty to perform psychophysical tests.